Were Allergic Diseases Prevalent in Antiquity? - GÖRKEY, ŞEFİK (BILIMSEL TIP YAYINEVI, 2018)
Allergic diseases are attributed to modern times and urban lifestyle. This manuscript discusses the narrations mentioned about suspected allergic disorders within Egyptian, Chinese, and Greco-Roman texts that represent the prominent civilizations of antiquity and also the quoted symptoms observed in some historically important figures, which might be considered as rudimentary case reports. The symptoms mentioned in ancient texts are only suggestive of allergic diseases. The present evidence is not conclusive enough to assert that allergic diseases were prevalent -at least not as much as today- in that age.
Keywords: Allergic rhinitis; asthma; history of medicine; urticaria